If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12p + -4 = 92 Reorder the terms: -4 + 12p = 92 Solving -4 + 12p = 92 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 12p = 92 + 4 Combine like terms: -4 + 4 = 0 0 + 12p = 92 + 4 12p = 92 + 4 Combine like terms: 92 + 4 = 96 12p = 96 Divide each side by '12'. p = 8 Simplifying p = 8
| 4b-6=38 | | .6(4x+6)=.7-(x-3) | | 12y^2-9y= | | 39-4x=7-8x | | 2(3+l)=14 | | 5p-17=2(2p-17) | | 6y+20+70=180 | | 7t+5=54 | | -6a+2+7a=7-26 | | (15x-18)=54 | | 8c-16=24 | | 9x+2x+3x-4=5x | | (4x-28)=56 | | 11x+5y=-19 | | .5(3x+7)=.6-(x-3) | | (3x)+(4x)=75 | | 3p+63=75 | | (12x+4)=(8x+32) | | (3x)+(4x)=65 | | 71=16w-8-9 | | -7/23+x=7/23 | | 52x^3-10x^2-8x= | | 6(n+9)=384 | | (12x+4)(8x+32)=360 | | 9+5x=-3+x | | ax+6=5(x-a) | | (12x+4)(8x+32)=180 | | n^2[n+1][2n^3+4n^2+n-1][n+6]=0 | | 12+3x=x-1 | | 68=x-0.21x | | x-6=4+3 | | 3x+2+2x=22 |